The role of proteins Stim and Orai as molecular components of the store-dependent current Ca2+ in lymphocytes - E. V. Lychkovskaya; A. N. Shuvaev; G. E. Gercog; L. V. Trufanova; L. B. Shadrina; A. A. Semenchukov; A. B. Salmina (Бюллетень сибирской медицины)
In the process of evolution of eukaryotes has formatted a highly organized mechanism for maintaining and regulating intracellular calcium homeostasis, which is one of the most important components of cell signaling in all branches of the phylogenetic tree. Intracellular calcium controls numerous physiological processes in the cell. Ca2+ forms signals as their spatial-temporal distribution. The frequency and amplitude of calcium oscillations depends on the signal strength. Calcium signals causing long-term or short-term responses of cells. Mainly, calcium signals in lymphocytes mediate gene expression program initiation that leads to proliferation, differentiation and production of proinflammatory cytokines also activate formation of inflammasome. Therefore, calcium signals mediate immune, and inflammatory response, autoimmune reaction of lymphocytes. The main mechanism of calcium signaling in lymphocytes is store-dependent Ca2+ current. Mobilization of cellular Ca2+ in response to receptor stimulation commonly occurs through release of Ca2+ ions from intracellular Ca2+ stores or influx across the plasma membrane through calcium - selective channels. Calciumselective channels are assembled from two protein families: the Orai proteins which form the ion channel pore, and the stromal interaction molecule (STIM) proteins which function as endoplasmic reticulum calcium sensors and activators of the channel. Stim protein is a transmembrane monomer which is localized at the membrane of the endoplasmic reticulum. This molecule is a sensor Ca2+ in response to emptying store activates calciumselective channels the plasma membrane. These channels express proteins Orai which are tetramers forming inside the channel pore and act as a site Ca2+. Orai binds to Stim. Orai proteins are activated after receiving information from Stim about Store depletion. Thus, the relationship and coordination of Stim and Orai proteins provides store - dependent Ca2+ current and causes cellular functional responses. Increased Ca2+ levels induce the activation of transcription factors such as NFAT, JNK1, MEF2, CREB, and, in most cases, is a crucial factor in the all differentiation or death. In this review, the mechanism of the store-dependent Ca2+ current in lymphocytes is presented.